2008
DOI: 10.1182/blood-2008-02-142158
|View full text |Cite
|
Sign up to set email alerts
|

Generation of enhanced stability factor VIII variants by replacement of charged residues at the A2 domain interface

Abstract: Factor VIII consists of a heavy chain (A1A2B domains) and light chain (A3C1C2 domains), whereas the contiguous A1A2 domains are separate subunits in the cofactor, factor VIIIa. The intrinsic instability of the cofactor results from weak affinity interactions of the A2 subunit within factor VIIIa. The charged residues Glu272, Asp519, Glu665, and Glu1984 appear buried at the interface of the A2 domain with either the A1 or A3 domain, and thus may impact protein stability. To determine the effects of these residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 37 publications
4
80
1
Order By: Relevance
“…5). However, Fay and co-workers demonstrated that replacement of residue Glu 665 for a valine or an alanine increases the stability of FVIIIa (24). This finding is in disagreement with the suggestion that interaction between Lys 1967 and Glu 665 contributes to the binding of the A2-a2 domain to the A1-a1/A3-C1-C2 dimer.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…5). However, Fay and co-workers demonstrated that replacement of residue Glu 665 for a valine or an alanine increases the stability of FVIIIa (24). This finding is in disagreement with the suggestion that interaction between Lys 1967 and Glu 665 contributes to the binding of the A2-a2 domain to the A1-a1/A3-C1-C2 dimer.…”
Section: Discussioncontrasting
confidence: 55%
“…For a number of hemophilia A variants carrying single amino acid substitutions, it has been suggested that a decreased stability of FVIIIa is the cause for the bleeding disorder (21,22). Employing molecular modeling studies on the available FVIII structures in combination with site-directed mutagenesis, Fay and co-workers have now successfully identified several amino acid residues that enhance or decrease the stability of FVIII (21,(23)(24)(25).…”
mentioning
confidence: 99%
“…In this assay the higher thermal stability variants also showed higher stability in this plasma assay (7). Further, the thrombin generation assays represent a good indicator of FVIIIa stability following thrombin activation and are monitored in a plasma-based assay.…”
Section: Discussionmentioning
confidence: 76%
“…The amount of thrombin generated in plasma was measured by Calibrated Automated Thrombography (28) using methods previously described (7). Briefly, FVIII deficient plasma (<1% residual activity, platelet-poor) from a severe hemophilia A patient lacking FVIII inhibitor (George King Bio-Medical) was mixed at 37ºC with a final concentration of 0.13 nM FVIII, 0.5 pM rTF, 4 μM PSPCPE vesicles, 433 μM fluorogenic substrate, 13.3 mM CaCl 2 , and 105 nM thrombin calibrator.…”
Section: Thrombin Generation Assaymentioning
confidence: 99%
See 1 more Smart Citation